Effectiveness of treatment programs for cyberaddiction in children and adolescents: systematic review and meta-analysis - Toro-Huamanchumo, Carlos J. (2022)
Introduction: The objective of this study was to evaluate the efficacy of treatment programs for cyberaddiction in children and adolescents. Material and Methods: Five databases were searched. Randomized controlled trials (RCTs) or cohort studies that evaluated the efficacy of treatment programs for cyberaddiction in children and adolescents were selected. The primary outcome was a decrease in hours of Internet use. For the meta-analysis, the random effects model with inverse variance method was used. Results: Seven articles were identified and included in the systematic review (3 randomized controlled trials and 4 retrospective cohorts), with a total of 2396 participants. The mean age was 14 years (SD 1.96). The duration of treatment among all published studies ranged from 4 days to 3 months. Cyberaddiction treatments were found to reduce hours of internet connection by 1.18 hours per week compared to any control treatment (MD 1.18; 95%CI -2.1825 to -0.1754; p= 0.02). Conclusions: Treatments for cyberaddiction, regardless of the type of intervention reduce hours of internet connection.